Frequency Domain Enhancement Filters: A Survey - Kanagalakshmi, K; Shenbagavadivu, S (International Journal of Computer Sciences and Engineering, 2025)
Fingerprints are majorly used to extract the physiological characteristics of human for identification and authentication purpose. Since the fingerprint became essential factor in day today life, features of fingerprints can be tainted which includes noises. Noise is a distortion and unwanted element of an image. It affects the accuracy of the biometric system in identifying and authenticating a person. Noises are of different types such as Gaussian, Salt and Pepper, Speckle noise etc. They are generated either due to internal or external factors. Noises are removed by applying various types of filtering techniques. Usually images are filtered based on the noises. Filters are applied in either spatial or frequency domain of the image. Frequency domain transformations are functions in Fourier transformations of image. This survey aims to identify the best suitable frequency domain filtering technique which is applied to enhance fingerprint quality